Aquaporin Positron Emission Tomography Differentiates Between Grade III and IV Human Astrocytoma. Issue 6 (21st June 2017) - Suzuki, Yuji; Nakamura, Yukihiro; Yamada, Kenichi; Kurabe, Satoshi; Okamoto, Kouichirou; Aoki, Hiroshi; Kitaura, Hiroki; Kakita, Akiyoshi; Fujii, Yukihiko; Huber, Vincent J; Igarashi, Hironaka; Kwee, Ingrid L; et al.
Abstract: BACKGROUND: Aquaporin (AQP) water channels play a significant role in mesenchymal microvascular proliferation and infiltrative growth. AQPs are highly expressed in malignant astrocytomas, and a positive correlation is observed between their expression levels and histological tumor grade. OBJECTIVE: To examine the utility of aquaporin positron emission tomography (PET) for differentiating between astrocytoma grade III and grade IV using the AQP radioligand [ 11 C]TGN-020. METHODS: Fifteen astrocytoma patients, grade III (n = 7) and grade IV (n = 8), and 10 healthy volunteers underwent [ 11 C]TGN-020 aquaporin PET imaging. Surgical tissues of astrocytoma patients were examined for histopathological grading using the WHO classification standard and expression of AQP1 and AQP4 immunohistochemically. RESULTS: Mean standardized uptake values of astrocytoma grade III and IV (0.51 ± 0.11 vs 1.50 ± 0.44, respectively) were higher than normal white matter (0.17 ± 0.02, P < .001) for both tumor grades. Importantly, mean standardized uptake values of astrocytoma grade IV were significantly higher than grade III ( P < .01). CONCLUSION: Our study demonstrated that [ 11 C]TGN-020 aquaporin PET imaging differentiated between astrocytoma grades III and IV. We suggest its clinical application as a noninvasive diagnostic tool would lead to advancements in the management of these malignant brain tumors.